NMR in Glycoscience and Glycotechnology 2017
DOI: 10.1039/9781782623946-00020
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spin-Couplings in Saccharides: Relationships Between Structure, Conformation and the Magnitudes ofJHH,JCH andJCC Values

Abstract: NMR spin–spin coupling constants (scalar couplings, J-couplings) are highly abundant in saccharides, with multiple values often reporting on the same structural domain (redundancy). While conventional analyses of J-couplings typically involve studies of these parameters in relation to individual structural elements, future treatments are more likely to involve simultaneous analyses of large numbers of redundant (and in some cases correlated) J-couplings sensitive to multiple structural domains, providing a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(100 citation statements)
references
References 84 publications
3
96
0
Order By: Relevance
“…The above findings confirm those of earlier studies 30-32,34,38,39,107 that different orientations ( i.e. , axial vs equatorial) of electronegative (hydroxyl) groups affect the parametrization of J -coupling equations when these groups are attached to internal and terminal carbons in the coupling pathway (Figures 3 and 5).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The above findings confirm those of earlier studies 30-32,34,38,39,107 that different orientations ( i.e. , axial vs equatorial) of electronegative (hydroxyl) groups affect the parametrization of J -coupling equations when these groups are attached to internal and terminal carbons in the coupling pathway (Figures 3 and 5).…”
Section: Resultssupporting
confidence: 90%
“…26-34 In this study, systematic effects caused by the second torsion angle were observed for some 3 J COCC values. Modeling these dual dependencies requires equations with at least one two-dimensional component to describe the significant features of the data adequately.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations